The muslims' response to the challenges of religious pluralism in Malaysia - Jamaludin, Najiah Athirah; Ibrahim, Haslina (IIUM Press, International Islamic University Malaysia, 2019)
This paper discusses the rise of Religious Pluralism in Malaysia in the light of Muslims‘ response perspective. The researcher seeks to explore the narrative of religious pluralism in Malaysia and to explain both the meaning and the historical background to objectively analyse their challenges to Muslim faith in Malaysia and thus explain the Muslims‘ response to it. This research is theoretical and philosophical, and therefore, is qualitative in nature and depends much on textual research. The resources include printed and online materials. To analyse the data, the researcher has adopted critical and analytical methods. The findings show that acceptance of religious pluralism by Muslims is the result of confusion and misinterpretation of texts on the origin, context and the challenges brought by the philosophy to religion, in particular to Islam, being the religion of the nation.